A simplified stationary energy-transport model with temperature-dependent conductivity. (June 2017) - Dong, Jianwei; Ju, Qiangchang
Abstract: A simplified stationary energy-transport model in semiconductors is studied while the conductivity depends on both electron density and temperature. The existence and uniqueness of classical solutions to the model is proved for small variations of electron density and temperature.